Green Synthesize and Characterization of Copper Nanoparticles Using Iranian Propolis Extracts - Yasamin Seyyed Hajizadeh; Naser Harzandi; Ebrahim Babapour; Mohsen Yazdanian; Reza Ranjbar (Advances in Materials Science and Engineering)
The propolis produced by bees is used by them to protect their hives. The cavity inside the hive’s walls is filled in during cold days to reduce entry points and mummify any intruders to ensure their survival. A current focus in nanotechnology and nanoscience is the green biosynthesis of nanoparticles (NPs) using biomaterials. Research on green methods for making metal oxide NPs is gaining momentum to safeguard the environment from the potential dangers associated with toxic chemicals. This study aimed to synthesize copper NPs (CuNPs) via propolis extraction, a novel application of nanoscience. The study was conducted under a range of pH, time conditions, and concentration ratios, and its properties were characterized by UV-Vis absorption spectra, XRD, and FTIR. An FTIR analysis revealed that compounds found in propolis extract could have an effect on the surface modification of the synthesized NPs. The propolis (Khalkhal) extract spectrum exhibited a sharp peak at 3422 cm−1, caused by free hydroxyl groups and their intra/intermolecular hydrogen bonds. There were sharp peaks at 2925, 1637, and 1515 to 1076 cm−1 associated with the C = O and C = C aromatic stretching frequencies. According to UV-Vis spectrophotometry investigation, CuO NPs exhibit a characteristic peak at 385 nm, showing significant surface plasmon resonance (SPR) with propolis (Khalkhal) extract. Furthermore, specific wavelengths of CuO NPs demonstrate peaks at 243, 292, and 350 nm for propolis (Gilan) extract. The green synthesis of CuNPs from Gilan and Khalkhal propolis can be an appropriate candidate for clinical applications such as drug delivery systems, drug formulation, and biomedical applications.